Preparation method of multi-layer alloy mesh electrode for hydrogen production by alkaline electrolysis of water and multi-layer alloy mesh electrode
By designing a multi-layer alloy grid electrode for hydrogen production with alkaline electrolytic water, the existing electrodes have been solved, and the existing electrodes have insufficient catalytic activity, slow bubble dissipation and insufficient durability stability have been achieved, and efficient and economical hydrogen production effect of electrolytic water production is achieved.
Patent Information
- Application Number
- CN202411888436.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-12-20
AI Technical Summary
The existing alkali water hydrogen production electrodes have insufficient catalytic activity, slow bubble emanation and insufficient durability and stability, which limit the rapid development of industrial alkali water hydrogen production technology.
Design an alkaline electrolytic water hydrogen-making multi-layer alloy mesh electrode. By selecting a nickel ferroalloy mesh and nickel molybdenum alloy mesh with a specific mass proportion, electrochemical etching and vacuum sintering treatment is carried out to form a three-layer electrode mesh structure, and The electrode surface is covered with a hydrophilic and gas-repellent layer.
The catalytic activity and bubble disengagement performance of the electrode are significantly improved, mechanical strength and durability are enhanced, and the efficient hydrogen production of water is achieved by electrolyzing water, reducing production costs and improving the long-term and efficient operation ability of the electrode.
Smart Images

Figure CN119433575A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an alkaline water electrolysis hydrogen production electrode, in particular to a preparation method of a multilayer alloy mesh electrode for alkaline water electrolysis hydrogen production and the multilayer alloy mesh electrode. Background Art
[0002] With the growth of global energy demand and the environmental problems caused by the use of fossil fuels, it is particularly important to find clean and renewable energy conversion technologies. Hydrogen, as a clean energy carrier, can be used for fuel cell power generation, transportation fuel, etc., to promote the development of the hydrogen economy. Hydrogen production by water electrolysis can be combined with renewable energy sources such as wind energy and solar energy to convert these energy sources into hydrogen that is easy to store and transport. Alkaline water electrolysis to produce hydrogen is currently the most mature and commercialized technology route. Among them, improving the efficiency of water electrolysis electrodes is the focus of current research. It is of great significance to develop new electrodes to reduce energy consumption and increase hydrogen production rate.
[0003] Traditional electrode materials, especially those using precious metals such as platinum and iridium, are expensive, which limits their economic viability in large-scale industrial applications. Currently, nickel mesh electrodes are mainly used in industry, with pure nickel mesh used for the anode and nickel mesh sprayed with Raney nickel for the cathode. In actual use, this form of electrode still has many problems.
[0004] First, the catalytic activity of the single-layer nickel mesh is insufficient. The slow kinetics of the four-electron oxygen evolution reaction (OER) at the anode severely limits the production of oxygen. The single-layer nickel mesh mainly relies on the intrinsic catalytic activity of the nickel element for oxygen evolution reaction, which has limited activity, a small active area, and few catalytic sites.
[0005] Secondly, the single-layer nickel mesh has a simple structure and poor bubble release performance. The hydrogen and oxygen produced by the electrolysis of water at the anode and cathode need to be quickly released from the electrode surface and discharged with the alkali solution to ensure good contact and reaction between the alkali solution and the electrode. The single-layer nickel mesh with a smooth surface has poor bubble release, causing gas to accumulate on the electrode surface. The number of bubbles between the solution and the electrode increases, and the ohmic impedance increases, resulting in increased voltage and energy consumption; bubbles cover active sites on the electrode surface, and the electrolysis efficiency decreases; excessive bubble accumulation may also cause pressure increases on both sides, increasing the risk of gas cross-talk.
[0006] Furthermore, the durability and stability of the cathode Raney nickel sprayed electrode is poor. Although the hydrogen evolution performance is improved to a certain extent after spraying Raney nickel, it also leads to a decrease in mechanical stability and contact performance. The contact between the sprayed Raney nickel catalyst and one side of the membrane becomes worse, increasing the contact resistance, and when the assembly pressure is too high, it may also cause membrane perforation. After running for a period of time, the Raney nickel electrode will have a powder loss problem, resulting in a decline in the overall performance of the electrolyzer.
[0007] In summary, the existing nickel mesh electrodes have many deficiencies in catalytic activity, bubble release structure, and durability and stability, which restrict the rapid development of industrial alkaline water hydrogen production technology. In view of this situation, there is an urgent need for a new type of electrode that can ensure the improvement of intrinsic activity while optimizing the bubble release structure, increasing mechanical strength and durability and stability, and realizing efficient water electrolysis hydrogen production. Summary of the invention
[0008] In order to solve the problems of poor catalytic activity, slow bubble escape and insufficient durability and stability of existing alkaline water hydrogen production electrodes, the present invention designs a new type of water electrolysis electrode, which includes the selection of a substrate, the design and matching of a multi-layer mesh structure and the subsequent optimization treatment of the electrode, which can significantly optimize the above-mentioned problems of existing single-layer nickel mesh electrodes.
[0009] The purpose of the present invention can be achieved by the following technical solutions:
[0010] The first aspect of the present invention provides a method for preparing a multilayer alloy mesh electrode for producing hydrogen by alkaline water electrolysis, comprising the following steps:
[0011] S1: Selection of alloy electrode mesh material: Select a nickel-iron alloy electrode mesh with a mass ratio of 50%-95% nickel and 5%-50% iron as the anode alloy mesh, or select a nickel-molybdenum alloy mesh with a mass ratio of 60%-95% nickel and 5%-40% molybdenum as the cathode alloy electrode mesh;
[0012] S2: Electrode mesh etching: The alloy electrode mesh obtained in S1 is used as an anode and an inert electrode is used as a cathode, and electrochemical etching is performed using a 0.5-5M acid solution to obtain an etched alloy electrode mesh;
[0013] S3: stacking a pure nickel mesh with a mesh number of 80-200 as the first layer, an alloy electrode mesh with a mesh number of 40-80 as the second layer, and an alloy electrode mesh with a mesh number of 20-40 as the third layer in sequence, and vacuum sintering at 800-1400° C. for 2-5 hours to obtain a multilayer alloy mesh electrode;
[0014] S4: Covering with a hydrophilic and air-repellent layer: The multilayer alloy mesh electrode obtained after sintering is placed in a polyethyleneimine aqueous solution, stirred, and dried to obtain a finished product of an alkaline water electrolysis hydrogen production multilayer alloy mesh electrode.
[0015] Furthermore, in S2, the acid solution includes hydrochloric acid or other acids, and the acid solution is used to prevent impurities from being generated on the electrode surface and covering the active sites during the etching process.
[0016] Furthermore, in S2, the inert electrode is a platinum sheet electrode, and double cathodes are arranged on both sides of the anode alloy mesh to ensure uniformity of etching on the electrode surface.
[0017] Furthermore, in S2, during the electrode mesh etching process, the etching temperature is controlled at 20-30°C, and when the current density is 10-60 mA / cm 2 When the current density is between 2A and 10A, the etching time is 20-60 minutes, and when the current density is between 2A and 10A, the etching time is 3-10 seconds, so as to regulate the surface morphology of the electrode.
[0018] Furthermore, in S3, the wire diameter of the pure nickel mesh in the first layer is smaller than the wire diameter of the alloy electrode mesh in the second layer, and the mesh density of the pure nickel mesh in the first layer is greater than the mesh density of the alloy electrode mesh in the second layer, so as to facilitate adaptation to the diaphragm and gas discharge.
[0019] Furthermore, in S3, the wire diameter of the alloy electrode mesh in the second layer is smaller than that in the third layer, and the mesh density of the alloy electrode mesh in the second layer is greater than that of the alloy electrode mesh in the third layer, thereby achieving a gradual transition of structural characteristics from the inner layer to the outer layer, which facilitates gas discharge.
[0020] Furthermore, in S3, during the vacuum sintering process, the sintering atmosphere is an inert gas atmosphere to prevent oxidation of the electrode material at high temperature and promote fusion between the layers of the electrode mesh.
[0021] Furthermore, in S3, the mass concentration of polyethyleneimine in the polyethyleneimine aqueous solution is 2%-5%;
[0022] In S3, the multilayer alloy mesh electrode obtained after sintering is stirred in a polyethyleneimine aqueous solution for 1 h to 3 h.
[0023] Furthermore, in S4, the drying includes: baking at 100-120°C for 10 minutes, then cross-linking polyethyleneimine with a 1wt% glutaraldehyde aqueous solution for 1 minute, and finally freeze-drying for 10 minutes. The formed hydrophilic and air-phobic layer has a mesh structure, and the pore size and distribution of the mesh structure are compatible with the electrode mesh structure to synergistically promote the rapid detachment of bubbles.
[0024] The second aspect of the present invention provides a multilayer alloy mesh electrode for producing hydrogen by alkaline water electrolysis obtained by the above-mentioned preparation method.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] First of all, in terms of electrode material selection, nickel-iron alloy mesh with a specific mass ratio is selected as the anode and nickel-molybdenum alloy mesh is selected as the cathode. These transition metal alloy materials are low in cost and suitable for large-scale production. Their activity and stability have been effectively improved compared to traditional materials. They can provide a good catalytic basis for water electrolysis reactions, significantly reducing production costs while ensuring the long-term and efficient operation of the electrodes.
[0027] Secondly, in the electrode mesh etching step, the roughness of the electrode surface and the number of active sites were successfully increased by precisely controlling the electrochemical etching conditions, including acid concentration, current density, and etching time. This not only greatly improved the catalytic performance of the electrode, allowing the electrolysis reaction to proceed more efficiently, but also optimized the bubble escape structure on the electrode surface, effectively solving the problem of slow bubble escape in traditional electrodes, reducing the increase in solution impedance caused by bubble attachment, and further improving electrolysis efficiency.
[0028] Furthermore, the unique three-layer electrode mesh structure design and processing played a key role. The pure nickel mesh with a mesh count of 80-200 as the first layer can fit tightly to the porous diaphragm to prevent the diaphragm from being punctured and causing serious hidden dangers of hydrogen and oxygen cross-talk, ensuring the safety and stability of the electrolysis process; the 40-80 mesh and 20-40 mesh etched alloy electrode meshes are used as the second and third layers respectively. The mesh count decreases from the inside to the outside and the wire diameter changes reasonably, forming a dense inner and sparse outer structure. This structure increases the solution-electrode contact area and provides sufficient reaction sites for the electrolysis reaction. At the same time, the large mesh structure of the outer layer facilitates the rapid discharge of gas, effectively improving the bubble escape performance, and the three-layer mesh is firmly bonded through high-temperature vacuum sintering. The overall mechanical stability is far better than that of the traditional single-layer nickel mesh, and it can withstand the impact of alkali solution during the electrolysis process and operate stably, greatly extending the service life of the electrode.
[0029] Finally, the hydrophilic and gas-repellent layer covering step uses a polyethyleneimine aqueous solution to treat the multilayer alloy mesh electrode to form a meshed hydrophilic and gas-repellent layer on the electrode surface. This layer can work synergistically with the electrode mesh structure to further promote the rapid detachment of bubbles from the electrode surface, significantly reducing the solution impedance caused by bubble aggregation, so that the entire electrode system always maintains a high efficiency during the water electrolysis process, further improving the comprehensive performance of the electrode of the present invention in the field of hydrogen production by alkaline water electrolysis, and providing solid technical support and guarantee for large-scale industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Schematic diagram of a multi-layer alloy mesh assembly according to Example 1 of the present invention, wherein the innermost layer is a 100-mesh nickel mesh, the middle layer is a 40-mesh nickel-iron alloy mesh, and the outer layer is a 20-mesh nickel-iron alloy mesh;
[0031] Figure 2 Figure 3 The front and back images of the multi-layer alloy mesh sintered together (not in this embodiment, for illustrative reference only);
[0032] Figure 4 This is a scanning electron microscope image of the surface of the alloy mesh without etching treatment in Example 1 of the present invention;
[0033] Figure 5This is a surface scanning electron microscope image of the 40-mesh nickel-iron alloy mesh of the intermediate layer of Example 1 of the present invention after etching;
[0034] Figure 6 This is a surface scanning electron microscope image of the outer layer 20-mesh nickel-iron alloy mesh after etching in Example 1 of the present invention;
[0035] Figure 7 This is a graph showing the oxygen evolution current-voltage curves of the multilayer electrode mesh of Example 1 of the present invention and a common single-layer 40-mesh nickel mesh. DETAILED DESCRIPTION
[0036] On the whole, the present invention is mainly achieved through the following technical solutions: first, the alkaline water electrolysis anode or cathode electrode materials are selected respectively, preferably transition metals with good catalytic performance for oxygen evolution reaction, because they have the advantages of low cost, suitable for large-scale production and good activity stability; then the electrode mesh is etched to increase the surface roughness of the electrode and the number of active sites, and optimize the bubble escape structure on the electrode surface; multiple layers of treated electrode meshes with different mesh sizes are selected to be superimposed and then sintered together to enhance the catalytic performance of the electrode, bubble escape performance and durable stability; finally, a hydrophilic and air-repellent polymer coating is performed to effectively help the bubble escape.
[0037] (1) Selection of electrode mesh:
[0038] Electrode mesh material:
[0039] The anode material is preferably a nickel-iron alloy mesh, in which nickel is the main element, accounting for 50%-95% by mass, and iron is the secondary element, accounting for 5%-50% by mass.
[0040] The cathode material is preferably a nickel-molybdenum alloy mesh, in which nickel is the main element, accounting for 60%-95% by mass, and molybdenum is the secondary element, accounting for 5%-40% by mass.
[0041] ②Electrode mesh structure:
[0042] The electrode designed in the present invention is composed of three layers of electrode nets, and the three parts respectively bear corresponding functions.
[0043] The first layer of pure nickel mesh: the mesh number is 80-200 mesh, which is characterized by denser mesh holes, smaller mesh wire diameter, and higher smoothness.
[0044] The second layer of alloy mesh: the mesh number is 40-80 mesh, the mesh size is medium, the mesh number is similar to the current commercial nickel mesh, and the wire diameter is moderate.
[0045] The third layer of alloy mesh: the mesh number is 20-40, the mesh is sparse, and the wire diameter is larger.
[0046] The main reason for choosing alloy material as the electrode alloy mesh substrate is that we have seen in relevant literature that transition metals are excellent materials for electrolyzing water to produce hydrogen, and two or more metals work synergistically to exert better electrolytic performance, that is, nickel-based alloys with nickel as the main element can exert better catalytic performance than pure nickel, such as nickel-iron alloys, which have lower costs than pure nickel.
[0047] The structure of the three-layer alloy mesh can provide a larger solution-electrode contact area, effectively improving the electrolysis efficiency. At the same time, the number of alloy meshes decreases from the inner porous membrane to the outer current plate side of the three-layer electrode mesh.
[0048] The inner layer near the membrane side uses a pure nickel mesh with a high mesh count. The role of this layer of nickel mesh is to ensure the perfect fit between the electrode and the porous diaphragm. The use of a high mesh count and small wire diameter nickel mesh can also effectively prevent the porous membrane from being pierced by the electrode mesh to prevent serious problems such as hydrogen and oxygen crosstalk. The middle layer uses an alloy mesh with a moderate mesh count similar to the commercial nickel mesh, which provides the main catalytic activity and improves the electrolysis efficiency. The alloy mesh can provide better performance than the pure nickel mesh, and has higher mechanical strength and durability. The outer layer uses a sparse alloy mesh with a larger mesh size and a larger wire diameter, which provides a similar role to the electrolytic cell flow channel, facilitating the rapid discharge of gas while producing gas on the surface electrolysis.
[0049] (2) Electrode mesh etching process:
[0050] Preparation of electrode mesh material and etching solution:
[0051] Select the middle layer and outer alloy mesh for etching (the inner layer does not need to be etched), prepare 0.5-5M hydrochloric acid (or other acid solution) as the etching solution, and use acid solution etching to effectively prevent impurities from being generated on the electrode surface during the etching process and covering the active sites.
[0052] Electrochemical etching:
[0053] Immerse the alloy mesh in the prepared etching solution, with the alloy mesh as the anode and the inert electrode (such as a platinum electrode) as the cathode. Set up a double cathode, placed on both sides of the anode alloy mesh to ensure uniform etching of the electrode surface.
[0054] The constant current electrochemical etching method is used to control the current density to produce different morphologies. 2 When the current density is between 2A and 10A, the electrochemical etching time is controlled to be 20-60 minutes; when the current density is between 2A and 10A, the etching time is 3-10 seconds.
[0055] The etching temperature is around room temperature, 20-30°C. Pay attention to ventilation of the surrounding environment during etching.
[0056] (3) Three-layer electrode mesh sintering:
[0057] After etching the alloy mesh, the inner nickel mesh and the middle and outer alloy meshes need to be sintered. The three layers of electrode mesh are stacked in order from large to small mesh size to form a multilayer electrode mesh structure with dense inner and sparse outer mesh. The multilayer mesh is then placed in a vacuum sintering furnace for sintering. The specific sintering conditions are: the temperature is controlled at 800-1400°C and the sintering time is 2-5 hours. Through vacuum sintering, the surface of the three layers of electrode mesh is slightly melted at high temperature and sticks together to form an integral structure.
[0058] The role of this electrode mesh structure is as follows: the inner layer of high-mesh nickel mesh fits tightly with the porous diaphragm, reducing contact impedance and preventing puncturing the diaphragm to cause hydrogen and oxygen cross-gassing; the middle layer of etched electrode effectively increases the active area of the electrode surface, and the etched electrode can expose more active sites. Compared with sprayed or deposited catalysts that are easy to fall off, the high active area obtained by this method is more stable and durable, and is suitable for large-scale industrial production. The surface of the outer layer of sparse alloy mesh is etched with striped morphology that is more conducive to gas escape, reducing the adsorption force of bubble escape. The three layers of electrode mesh are cleverly combined to exert better electrolysis performance.
[0059] (4) Hydrophilic and air-repellent layer coverage:
[0060] To obtain better bubble escape performance, the multilayer electrode mesh obtained in step (3) is further subjected to hydrophilic and gas-repellent treatment. Polyethyleneimine (PEI) has good hydrophilic and gas-repellent properties, which can effectively help bubbles escape quickly from the electrode surface and prevent the increase in solution impedance caused by a large number of bubbles gathering.
[0061] Place the multilayer electrode mesh in a 2%-5% polyethyleneimine aqueous solution and gently stir for 1h-3h;
[0062] After taking it out, bake it at 100-120℃ for about 10 minutes to obtain better adhesion between polyethyleneimine and the substrate;
[0063] Polyethyleneimine was cross-linked with 1 wt % glutaraldehyde aqueous solution for 1 min to produce a Schiff base condensation reaction (as shown below);
[0064] R-CHO+R′-NH 2 →RC=NR′+H 2 O
[0065] Finally, freeze-dry for 10 minutes and take it out.
[0066] The obtained multilayer net covered with a layer of mesh polyethyleneimine has excellent electrolytic performance and can quickly discharge bubbles.
[0067] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. Any features such as preparation means, materials, structures or composition ratios not clearly described in this technical solution are regarded as common technical features disclosed in the prior art.
[0068] Example 1
[0069] (1) Multilayer alloy mesh selection
[0070] Base material (this embodiment takes the anode electrode mesh for water electrolysis as an example):
[0071] The first layer is 100 mesh nickel screen;
[0072] The second layer is a 40-mesh nickel-iron alloy mesh, wherein the nickel-iron alloy mesh has a mass ratio of 80% nickel and 20% iron;
[0073] The third layer is a 20-mesh nickel-iron alloy mesh, wherein the nickel-iron alloy mesh has a mass ratio of 80% nickel and 20% iron;
[0074] The size is 2cm*2cm;
[0075] Etching solution: prepare 1M and 3M dilute hydrochloric acid solutions;
[0076] Figure 1 Schematic diagram of a multi-layer alloy mesh assembly according to Example 1 of the present invention, wherein the innermost layer is a 100-mesh nickel mesh, the middle layer is a 40-mesh nickel-iron alloy mesh, and the outer layer is a 20-mesh nickel-iron alloy mesh; Figure 2 Figure 3 The front and back images are of a multi-layer alloy mesh sintered together (not this embodiment, for illustrative reference only).
[0077] (2) Alloy mesh etching
[0078] Preprocessing:
[0079] First, the alloy mesh materials were simply pretreated, that is, the alloy meshes (40 mesh and 20 mesh) were ultrasonically cleaned with 1M hydrochloric acid, then rinsed with deionized water, and then ultrasonically cleaned with anhydrous ethanol for 15 minutes. After air drying, etching could be started.
[0080] Etching process:
[0081] Etching treatment of the second layer of 40 mesh nickel-iron alloy mesh:
[0082] The nickel-iron alloy mesh was immersed in 3M hydrochloric acid for 24 hours to construct a certain etching site, then taken out and ultrasonically cleaned with deionized water for 10 minutes, and air-dried for use;
[0083] Use two platinum electrodes as cathodes, with a size of 2cm*2cm, and a nickel-iron alloy mesh as an anode, and immerse them in 1M hydrochloric acid etching solution. The nickel-iron alloy mesh anode is placed between the two cathodes to ensure that the three electrodes are facing each other and at the same distance, in order to ensure the uniformity of the etching effect;
[0084] Configure a constant current power supply and set the current density to 5A / cm 2 , power-on etching time 10s;
[0085] During the electrochemical etching process, a constant temperature water bath device is used to ensure that the etching solution temperature is 20-30°C;
[0086] After etching, take out the nickel-iron alloy mesh, rinse the etching solution with deionized water, and air-dry. The surface morphology of the obtained alloy mesh is as follows: Figure 5 shown.
[0087] Etching treatment of the third layer of 20 mesh nickel-iron alloy mesh:
[0088] Use two platinum electrodes as cathodes, with a size of 2cm*2cm, and a nickel-iron alloy mesh as an anode, and immerse them in 1M hydrochloric acid etching solution. The nickel-iron alloy mesh anode is placed between the two cathodes to ensure that the three electrodes are facing each other and at the same distance, in order to ensure the uniformity of the etching effect;
[0089] Configure a constant current power supply, set the current density to 20mA / cm, and the etching time to 30min;
[0090] During the electrochemical etching process, a constant temperature water bath device is used to ensure that the etching solution temperature is 20-30°C;
[0091] After etching, take out the nickel-iron alloy mesh, rinse the etching solution with deionized water, and air-dry. The surface morphology of the obtained alloy mesh is as follows: Figure 6 shown.
[0092] (3) Sintering treatment
[0093] The nickel mesh and the two layers of etched nickel-iron alloy mesh are stacked in sequence, and the three-layer electrode is quickly sintered as a whole. The sintering temperature is set to 1100°C, the sintering time is 3 hours, and then the temperature is slowly lowered to solidify.
[0094] This sintering condition is suitable for the three-layer electrode mesh structure of this component, which can make the contact parts of the three-layer electrode mesh slightly melt under high temperature conditions and firmly combine them together when the temperature drops to form an integral electrode structure.
[0095] (4) Hydrophilic and air-repellent layer coverage:
[0096] Cover both sides of the multilayer electrode mesh with raw tape (the two sides of the electrode mesh are in contact with the porous membrane and the electrode plate respectively, and in order to obtain good contact performance, there is no need to cover the hydrophilic and air-repellent layer), put it into a 3wt% polyethyleneimine aqueous solution and gently stir it for 2h;
[0097] After taking it out, bake it in an oven at 100°C for 10 minutes to ensure good adhesion between the polyethyleneimine and the substrate;
[0098] The polyethyleneimine was cross-linked with a 1 wt % glutaraldehyde aqueous solution for 1 min to form a mesh-like hydrophilic and air-repellent layer on the surface of the electrode mesh;
[0099] Finally, dry it for 10 minutes and then take it out.
[0100] The obtained multilayer net covered with a layer of mesh polyethyleneimine has excellent electrolytic performance and can quickly discharge bubbles.
[0101] Through the above steps, a multilayer electrode network with an etched structure, a hydrophilic and gas-repellent layer and optimized materials can be obtained.
[0102] (5) Electrode performance characterization:
[0103] Scanning Electron Microscope (SEM) Characterization:
[0104] The surface morphology of the nickel-iron alloy mesh electrode was observed using SEM, and its microstructure and surface roughness were analyzed. Figure 4 , Figure 5 , Figure 6 shown.
[0105] Linear Sweep Voltammetry (LSV) Test:
[0106] The LSV test was carried out on an electrochemical workstation, using 1M KOH solution as the electrolyte, with a test range of 0V to 2V (relative to the standard hydrogen electrode) and a scan rate of 10mV / s. The LSV curve shows that the electrode of the present invention has a low oxygen evolution overpotential in the process of water electrolysis and excellent catalytic activity, such as Figure 7 shown.
[0107] Verification and explanation of this embodiment:
[0108] The above examples provide a three-layer alloy mesh with excellent performance:
[0109] The inner layer is a smooth and dense nickel mesh, which facilitates good contact with the diaphragm, maintains good conductivity, and helps reduce the impedance caused by contact;
[0110] The middle layer is an etched 40-mesh nickel-iron alloy mesh, such as Figure 5As shown in Figure 2, its surface has a regular pit-like structure, which can effectively increase the active surface area of the electrode, which is better than the smooth surface of the original alloy mesh ( Figure 4 ) is more conducive to improving electrolysis efficiency;
[0111] The outer layer is an etched 20-mesh nickel-iron alloy mesh, such as Figure 6 As shown, the prismatic structure on the surface can effectively reduce the adhesion force of bubbles, help the generated bubbles to quickly escape from the electrode surface, reduce the coverage time of bubbles on active sites and the increase in solution impedance due to bubbles;
[0112] The sintering step firmly combines the three-layer electrode mesh, and the etching has a more stable surface structure than the traditional deposition method. This is the key part of in-situ etching that is superior to the external catalyst "depositing" on the surface of the electrode mesh. After etching, the original material components and optimized structure are maintained, while the catalyst loaded by deposition and other methods obviously do not have this firmness and stability.
[0113] Finally, covering with a hydrophilic and air-repellent layer will further enhance the hydrophilic and air-repellent properties of the electrode mesh as a whole, help the electrode catalytic sites to have good contact and reaction with the solution, and quickly discharge the generated bubbles, thereby achieving the purpose of improving the electrolysis efficiency. The oxygen evolution performance of the actual three-electrode test also confirms the great improvement in the oxygen evolution performance of the electrode in Example 1 of the present invention in water electrolysis.
[0114] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing a multilayer alloy mesh electrode for producing hydrogen by alkaline water electrolysis, characterized in that: The following steps are involved: S1: Selection of alloy electrode mesh material: Select a nickel-iron alloy electrode mesh with a mass ratio of 50%-95% nickel and 5%-50% iron as the anode alloy mesh, or select a nickel-molybdenum alloy mesh with a mass ratio of 60%-95% nickel and 5%-40% molybdenum as the cathode alloy electrode mesh; S2: Electrode mesh etching: The alloy electrode mesh obtained in S1 is used as an anode and an inert electrode is used as a cathode, and electrochemical etching is performed using a 0.5-5M acid solution to obtain an etched alloy electrode mesh; S3: stacking a pure nickel mesh with a mesh number of 80-200 as the first layer, an alloy electrode mesh with a mesh number of 40-80 as the second layer, and an alloy electrode mesh with a mesh number of 20-40 as the third layer in sequence, and vacuum sintering at 800-1400° C. for 2-5 hours to fuse the three layers of mesh, cool and solidify, and tightly combine to obtain a multilayer alloy mesh electrode; S4: Covering with a hydrophilic and air-repellent layer: The multilayer alloy mesh electrode obtained after sintering is placed in a polyethyleneimine aqueous solution, stirred, and dried to obtain a finished product of an alkaline water electrolysis hydrogen production multilayer alloy mesh electrode.
2. The method for preparing a multilayer alloy mesh electrode for producing hydrogen by alkaline water electrolysis according to claim 1, characterized in that: In S2, the acid solution is a hydrochloric acid solution including hydrochloric acid, and the acid solution is used to prevent impurities from being generated on the electrode surface during etching and covering the active sites. The hydrochloric acid solution is used to prevent impurities from being generated on the electrode surface during etching and covering the active sites.
3. The method for preparing a multilayer alloy mesh electrode for producing hydrogen by alkaline water electrolysis according to claim 1, characterized in that: In S2, the inert electrode is a platinum sheet electrode, and double cathodes are arranged on both sides of the anode alloy mesh to ensure uniformity of etching on the electrode surface.
4. The method for preparing a multilayer alloy mesh electrode for producing hydrogen by alkaline water electrolysis according to claim 1, characterized in that: In S2, during the electrode mesh etching process, the etching temperature is controlled at 20-30°C, and when the current density is 10-60mA / cm 2 When the current density is between 2A and 10A, the etching time is 20-60 minutes, and when the current density is between 2A and 10A, the etching time is 3-10 seconds, so as to regulate the surface morphology of the electrode.
5. The method for preparing a multilayer alloy mesh electrode for producing hydrogen by alkaline water electrolysis according to claim 1, characterized in that: In S3, the wire diameter of the pure nickel mesh in the first layer is smaller than the wire diameter of the alloy electrode mesh in the second layer, and the mesh density of the pure nickel mesh in the first layer is greater than the mesh density of the alloy electrode mesh in the second layer, so as to facilitate adaptation to the diaphragm and gas discharge.
6. The method for preparing a multilayer alloy mesh electrode for producing hydrogen by alkaline water electrolysis according to claim 1, characterized in that: In S3, the wire diameter of the alloy electrode mesh in the second layer is smaller than that in the third layer, and the mesh density of the alloy electrode mesh in the second layer is greater than that of the alloy electrode mesh in the third layer, thereby achieving a gradual transition of structural characteristics from the inner layer to the outer layer, which is convenient for gas discharge.
7. The method for preparing a multilayer alloy mesh electrode for producing hydrogen by alkaline water electrolysis according to claim 1, characterized in that: In S3, during the vacuum sintering process, the sintering atmosphere is an inert gas atmosphere to prevent oxidation of the electrode material at high temperature and promote fusion between the layers of the electrode mesh.
8. The method for preparing a multilayer alloy mesh electrode for producing hydrogen by alkaline water electrolysis according to claim 1, characterized in that: In S3, the mass concentration of polyethyleneimine in the polyethyleneimine aqueous solution is 2%-5%; In S3, the multilayer alloy mesh electrode obtained after sintering is stirred in a polyethyleneimine aqueous solution for 1 h to 3 h.
9. The method for preparing a multilayer alloy mesh electrode for producing hydrogen by alkaline water electrolysis according to claim 1, characterized in that: In S4, the drying includes: baking at 100-120°C for 10 minutes, then cross-linking polyethyleneimine with a 1wt% glutaraldehyde aqueous solution for 1 minute, and finally freeze-drying for 10 minutes. The formed hydrophilic and air-repellent layer has a mesh structure, and the pore size and distribution of the mesh structure are compatible with the electrode mesh structure to synergistically promote the rapid detachment of bubbles.
10. A multi-layer alloy mesh electrode for producing hydrogen by alkaline water electrolysis obtained by the preparation method as claimed in any one of claims 1 to 9.
Citation Information
Patent Citations
Novel two-dimensional transition metal boride, preparation method thereof and application of novel two-dimensional transition metal boride as energy storage electrode material
CN114956108A
Carbon-doped composite metal oxide oxygen evolution anode for electrolyzing carbon dioxide and preparation method of carbon-doped composite metal oxide oxygen evolution anode
CN118547331A
Multi-layer nickel net catalytic electrode for hydrogen production by alkaline electrolysis of water and preparation method of multi-layer nickel net catalytic electrode
CN119082763A
Electrode catalyst layer for carbon dioxide electrolysis cell, electrolysis cell and carbon dioxide electrolysis apparatus comprising the same
US20210292921A1
Bipolar electrolytic vessel, bipolar electrolytic vessel for alkali water electrolysis, and method for manufacturing hydrogen
WO2018139610A1
Cited By
Composite woven porous electrode as well as electrolytic bath, electrolysis device and method applying composite woven porous electrode
CN120174399A